2017
DOI: 10.1021/acsami.7b12992
|View full text |Cite
|
Sign up to set email alerts
|

Metallic versus Semiconducting SWCNT Chemiresistors: A Case for Separated SWCNTs Wrapped by a Metallosupramolecular Polymer

Abstract: As-synthesized single-walled carbon nanotubes (SWCNTs) are a mixture of metallic and semiconducting tubes, and separation is essential to improve the performances of SWCNT-based electric devices. Our chemical sensor monitors the conductivity of an SWCNT network, wherein each tube is wrapped by an insulating metallosupramolecular polymer (MSP). Vapors of strong electrophiles such as diethyl chlorophosphate (DECP), a nerve agent simulant, can trigger the disassembly of MSPs, resulting in conductive SWCNT pathway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 35 publications
1
37
0
1
Order By: Relevance
“…The conductances of metallic CNTs are less perturbative to external stimuli as a result of the difficulty in quenching the metallic state. 36…”
Section: Resultsmentioning
confidence: 99%
“…The conductances of metallic CNTs are less perturbative to external stimuli as a result of the difficulty in quenching the metallic state. 36…”
Section: Resultsmentioning
confidence: 99%
“…105 Swager and co-workers showed that conjugated polymers attached to selector side chains can provide selectively for the detection specific analytes and even resolve very similar structural isomers. 47,73,97,106,107 CNTs can also be functionalized with polymeric surfactants containing long alkyl chains that interact via hydrophobic interactions. 108,109 Dai and co-workers demonstrated the adsorption of Tween 20 conjugates containing biotin, staphylococcal protein A (SpA), or human autoantigen U1A to CNTs.…”
Section: Introduction and Scopementioning
confidence: 99%
“…Chemie pending upon the orientation of the graphene p-system with respect to the SWCNT axis,t he materials may be intrinsic metals or semiconductors.C hemiresistors with modes of action dominated by carrier injection/depletion/pinning will be most sensitive with semiconductive SWCNTs. [32] Metallic SWCNTs need not be charged to conduct, and as aresult are less susceptible to charge transfer processes,b ut also experience less interference from humidity.S ensors that operate solely on modulating the junctions between SWCNTs will be less sensitive to the nature of the carbon nanotubes.…”
Section: Methodsmentioning
confidence: 99%